Regenerative Potential of Stem Cell Therapy in Mitigating Brain Cell Atrophy and Enhancing Neuroprotection in Neurodegenerative Diseases - E, Rahul; Nupur Sinha; Vishnu M G (Jurnal Vokasi Kesehatan, 2024)
Stem cell therapy has shown great potential in regenerating neurons in the brain, offering hope for the treatment of neurodegenerative diseases characterized by progressive neuronal atrophy. These therapies target key mechanisms of neuronal loss, including protein aggregation, oxidative stress, and inflammation, while promoting neuroprotection through neurogenesis and angiogenesis. The development of induced pluripotent stem cells (iPSCs) has addressed challenges related to immune rejection and ethical concerns associated with the use of embryonic stem cells. Despite advancements, challenges such as immune responses, tumorigenesis risks, and efficient delivery methods remain. Future research should focus on optimizing cell sources, improving targeted delivery systems, and exploring combination therapies to enhance treatment efficacy and safety. With successful integration, stem cell therapy has the potential to revolutionize the management of neurodegenerative diseases, ultimately improving patient outcomes and quality of life.